Future selection of additional CCAFS target regions - Thornton, Philip K. (2011)
The original choice of the three target regions for CCAFS started from the understanding that South Asia and Africa are particularly vulnerable to climate change and deserving of priority attention. To summarise, of the various candidates in these two parts of the world, the decision to select three reflected a balance between two competing considerations: (i) working across contexts that are sufficiently heterogeneous to ensure that outputs and outcomes of place based research have global relevance, and (ii) ensuring that sufficient resources are brought to bear to address the deliberately complex problems that CCAFS seeks to address. The initial region selection process sought to sample across the challenges of major hydro meteorological shocks, significant climate related environmental problems, and high rural poverty rates coupled with large populations dependent on rainfed subsistence agriculture. Other factors included were the strength of national and regional climate institutions and processes that can support climate information for adaptation, the degree of CGIAR presence, overall progress toward food security goals, and opportunities for synergistic research with the potential for both immediate regional benefits and transferability beyond the regions. For the future, similar considerations could be applied. As before, projected future climate change is not likely to be a strong discriminator among candidate regions, as all regions are expected to warm, future rainfall trends are subject to considerable uncertainty, and changes in climatology are not likely to be detectable for the next ten years at least.